Being Smarter about Space: Drawing Lessons from Spatial Science. Issue 2 (3rd March 2020) - Poorthuis, Ate; Zook, Matthew
Abstract : Smart technology—in its many facets—is often critiqued within geography in ways that parallel the critiques of quantitative geography in the 1960s and GIScience in the 1990s. In this way, both the development of "smart" technology itself and its criticisms are the latest chapter in a long-standing disciplinary debate around quantification and technology. We reevaluate this history and argue that quantitative methodology and its theoretical critiques are not as incompatible as often claimed. To illustrate how we might address this apparent tension between theory and quantitative methods, we review how both approaches conceptualize one of geography's core concepts—space—and highlight opportunities for symbiosis. Although smart technologies can further orthodox positivist approaches, we argue that the actual practice is more nuanced and not necessarily absolute or totalizing. For example, recent computational work builds on critical geographic theories to analyze and visualize topological and relational spaces, relevant to topics such as gentrification and segregation. The result is not a geography in which smart technology and algorithms remove the need for human input but rather a rejoinder in line with the recent resurgence of a critical quantitative geography. In short, the result is a geography where social theory and the human intellect play a key role in guiding computational approaches to analyze the largest, most versatile, most and relevant data sets on social space that we have ever had. Key Words: geocomputation, GIScience, smart technology, space, spatial science.